2017
DOI: 10.1002/jgt.22103
|View full text |Cite
|
Sign up to set email alerts
|

Parity Linkage and the Erdős–Pósa Property of Odd Cycles through Prescribed Vertices in Highly Connected Graphs

Abstract: We show the following for every sufficiently connected graph G, any vertex subset S of G, and given integer k: there are k disjoint odd cycles in G each containing a vertex of S or there is set X of at most 2k−2 vertices such that G−X does not contain any odd cycle that contains a vertex of S. We prove this via an extension of Kawarabayashi and Reed's result about parity‐k‐linked graphs (Combinatorica 29, 215–225). From this result, it is easy to deduce several other well‐known results about the Erdős–Pósa pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…As discussed in Section 3.2, an analogue of the Erdős-Pósa theorem does not hold for the cycles described in Theorem 1.1. It was shown that in graphs of sufficiently high connectivity [11,13,18,30], an analogue of the Erdős-Pósa theorem holds for odd cycles. We ask whether a similar phenomenon happens for the cycles described in Theorem 1.1.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed in Section 3.2, an analogue of the Erdős-Pósa theorem does not hold for the cycles described in Theorem 1.1. It was shown that in graphs of sufficiently high connectivity [11,13,18,30], an analogue of the Erdős-Pósa theorem holds for odd cycles. We ask whether a similar phenomenon happens for the cycles described in Theorem 1.1.…”
Section: Discussionmentioning
confidence: 99%
“…Erdős-Pósa Property of Obstructions to Interval Graphs graphs for which the family of odd cycles (subgraphs and induced subgraphs) admits the Erdős-Pósa property. This includes planar graphs [15], or graphs with certain connectivity constraints [48,36,28,24]. Not only the family of odd cycles does not admit the Erdős-Pósa property, but also subfamilies such as the family of chordless cycles of length at least 5 [25].…”
Section: :4mentioning
confidence: 99%
“…Since the emergence of the result of Erdős and Pósa [14], a multitude of studies on the Erdős-Pósa property have appeared in the literature for several combinatorial objects beyond graphs. This includes extensions to digraphs [32,44,40,22,20], rooted graphs [9,26,35,24], labeled graphs [29], signed graphs [23,3], hypergraphs [1,6,7], matroids [16], helly-type theorems [21], H-minors [41], H-immersions [17,31], and H-butterfly directed minors [2] (also see [38]). This list is not comprehensive but rather illustrative.…”
Section: Introductionmentioning
confidence: 99%
“…Just as odd cycles, odd -cycles do not have the Erdős-Pósa property in general, but gain it in highly connected graphs; see [12]. For cycles in digraphs the situation is slightly different as demonstrated by an example of Wollan (see Kakimura and Kawarabayashi [13]): while (directed) cycles in digraphs have the Erdős-Pósa property, the property is lost when cycles are replaced by -cycles.…”
Section: Theorem 4 Let and Be Integers For Any Graph And Any Subsetmentioning
confidence: 99%